2017
DOI: 10.1016/j.exphem.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of fetal hematopoietic stem cell function in the absence of Fancd2

Abstract: Fanconi Anemia (FA), results from mutations in genes necessary for DNA damage repair and often leads to progressive bone marrow failure. Although the exhaustion of the bone marrow leads to cytopenias in FA patients as they age, evidence from human FA and mouse model fetal livers suggests hematopoietic defects originate in utero which may lead to deficient seeding of the bone marrow. To address this possibility, we examined the consequences of loss of Fancd2, a central component of the FA pathway. Examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
5
6
0
Order By: Relevance
“…Moreover, since I −/− and ID2 DKO cells are equally resistant to HU or APH despite harboring different residual chromatin-bound FANCD2 levels, FANCD2’s role in preventing APH/HU-induced cell death may in fact not depend on its own chromatin association. Consistent with our findings and interpretation, a role for FANCD2 in preventing apoptosis and cell death was also suggested by several groups ( 70 72 ). Moreover, a recent study showed that siRNA-mediated knockdown of FANCI, but not FANCD2, substantially reduced cellular apoptosis after UV treatment ( 67 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, since I −/− and ID2 DKO cells are equally resistant to HU or APH despite harboring different residual chromatin-bound FANCD2 levels, FANCD2’s role in preventing APH/HU-induced cell death may in fact not depend on its own chromatin association. Consistent with our findings and interpretation, a role for FANCD2 in preventing apoptosis and cell death was also suggested by several groups ( 70 72 ). Moreover, a recent study showed that siRNA-mediated knockdown of FANCI, but not FANCD2, substantially reduced cellular apoptosis after UV treatment ( 67 ).…”
Section: Discussionsupporting
confidence: 93%
“…Fancg −/− embryos were obtained at a lower frequency than expected at E11.5 and E12.5 (20% and 21.7%, respectively, instead of 25%, 958 embryos tested in total; p < 0.001). As observed in Fancc −/− and Fancd2 −/− mice ( Kamimae-Lanning et al., 2013 , Suzuki et al., 2017 ), this frequency dramatically declined at birth (11% ± 0.8, 82 postnatal day 0 [P0] to P1 pups tested, p < 0.001), suggesting a late perinatal lethality. Interestingly, at E11.5 and E12.5 Fancg −/− embryos were systematically smaller than wild-type (WT) control littermates, while at E14.5 only half of the Fancg −/− embryos remained smaller than control ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 51%
“…However, a deficit in the CD34 + cell numbers in FA subjects is observed very early during childhood, even before the onset of the BMF clinical symptoms ( Ceccaldi et al., 2012 , Kelly et al., 2007 ). This, added to the early developmental defects of the hematopoietic commitment described for human embryonic stem cells after knockdown of FANCA and FANCD2 genes, led us and others to hypothesize that the FA hematopoietic defect could already begin in utero ( Ceccaldi et al., 2012 , Kamimae-Lanning et al., 2013 , Suzuki et al., 2017 , Tulpule et al., 2010 , Yoon et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…That functionally corrective somatic mutations in a single human HSC prenatally are capable of completely replacing the hematopoietic tissues in twins by the time of birth 62 is conclusive proof that the repopulating capacity and overall fitness of the mutant HSCs are unambiguously reduced during development and can be overtaken by even one HSC in which the mutation has been corrected. This conclusion has been confirmed in human embryonic stem cells 63 and Fancc –/– and Fancd2 –/– mice 64 , 65 . The experiment of nature 62 provides clear theoretical evidence that if a single corrected stem cell can so massively outperform all of the mutant ones during development, gene therapy for this disease early in life (or perhaps in utero 66 ) can be successful in the future.…”
Section: Hematopoietic Defects and The Prospects Of Gene Therapysupporting
confidence: 53%